Improving value in health care measuring quality. - Organisation for Economic Co-operation and Development (France Organisation for Economic Co-operation and Development, 2010)
Are breast cancer survival rates higher in the United States than in the United Kingdom and France? Are a patient's chances of dying within 30 days after admission to a hospital with a heart attack lower in Canada than in Korea? Are surgeons in some countries more likely to leave "foreign bodies" behind after operations or make accidental punctures or lacerations rates when performing surgery? The need for answers to these kinds of question and the value of measuring the quality of health care are among the issues addressed in this publication.
Why do we need information on health care quality? -- What does existing data on health quality show? -- How can national health information infrastructures improve the measurement of quality of care? -- How can quality indicators be used to health system improvement? -- Conclusions and recommendations.
Includes bibliographic references.
Keywords: Medical care -- Quality control; Medical care -- Evaluation